The Creation and Trade of Value in the Coffee Value Chain in Uganda - Honstede, Merijn L. van; Wickert, Christopher; Katamba, David; Seruma, Andrew (AGRI-QUEST, 2016)
Stakeholder theory focuses on the creation and trade of value and how stakeholders jointly interact to create this value. What is still largely unexplored however is how stakeholders can create and trade this value? Moreover, how is value given sense to and made sense of and how do stakeholders interpret the concept of value? Method: This was tested through interviewing stakeholders in the coffee value chain in Uganda, alongside supporting documents to triangulate the empirical data found. Findings: Stakeholders seems to enable creation and trade of value by coffee production improvements, farmers’ income enhancement and social environment utilization of stakeholders. Inhibiting factors are suggested to be the characteristics of farmers and resource limitations faced by stakeholders. Most sensegiving efforts of production education, Training of Trainees and example farms are suggested to come from cooperatives and external actors and were either accepted or rejected by chain actors. Stakeholders interpret value differently as cooperatives and external actors’ utility function seem to be driven by economic, social and ecological values whereas chain actors were more driven by economic and social values. Implications: This research has shed more light on how stakeholders create and trade value, the concept of value, and how value is given sense to and made sense of. This has implications stakeholder theory researchers and practitioners active in cooperatives or external roles in agricultural chains as well as wider implications for other sectors and countries.
Keywords: Creation; Trade; Value; Coffee Value Chain